Canadian Annual Review of Politics and Public Affairs 1967 - Saywell, John T., 1929-2011 (Book collections on Project MUSE., 1968)
Convenient, authoritative, exceptionally readable and useful, its contents provide a dependable shortcut to the current history of Canada for a period hat cannot be dealt with fully by other references for many years.